Determinants of CSR funds in mining companies listed on the IDX for the 2017-2021 period - Cahya Prabowo, Nimas Sagita; Kusumawardhani, Indra (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2022)
This study aims to examine the effect of slack resources, tax aggressiveness and ISO 14001 certification on corporate social responsibility funds. The population of this study are mining companies listed on the Indonesia Stock Exchange (IDX). The sampling method in this study used non-probability sampling with the sampling technique using purposive sampling technique. The sample in this study were 111 mining companies. The analytical method in this study used multiple linear regression analysis to test the hypothesis. The results showed that slack resources had an effect on CSR funds, while tax aggressiveness had no effect on CSR funds and ISO 14001 certification had no effect on CSR funds. The results of this study can be used as a basis and consideration for the government in making regulations regarding CSR funds that must be issued by companies, so as to provide justice for the surrounding community who are affected by the company's operational activities.